Cuadro de la Portada: Autora: MARÍA BENCOMO. Título: “La aurora del ensayo” - Romero Salazar, Alexis (Espacio Abierto, 2025)
Cuadro de la Portada:Autora: MARÍA BENCOMOTítulo: “La aurora del ensayo”Técnica: Acrílico/telaMedidas: 1 x 1 m.Año: 2024